Energy-water nexus planning of regional electric power system within an inexact optimization model in Tangshan City, China. (1st September 2020) - Zhen, J.L.; Wu, C.B.; Liu, X.R.; Huang, G.H.; Liu, Z.P.
Abstract: Under the increasingly serious energy and water resources crisis, the correlation between two resources has become more and more close. Promoting the sustainable development of energy and water resources has been an inevitable choice for regional energy system planning. In this study, a hybrid interval two-stage fuzzy credibility constrained programming (ITFCP) model is developed for supporting energy-water nexus system management. ITFCP can explicitly address system uncertainties presented as probability distributions, fuzzy sets, and intervals, as well as dual dynamics through the concept of solutions with interval membership function. The method could provide effective linkages between predefined policies and economic penalties as well as system economy and risk. Then, ITFCP is applied to electric power system management under considering energy-water nexus in Tangshan City, which is a typical resource-based, high pollution, and water-deficient region in China. Multiple scenarios of different credibility levels about water availability are designed. Results disclosed that coal-fired power and imported electricity would play primary role in meeting tremendous electricity demand under the current situation. Results also revealed that the total water consumption control would be an effective way to accelerate electric power structural adjustment, protect energy and water resources as well as improve atmospheric environment. These findings are valuable for decision makers to gain in-depth analysis for more reasonable and applicable development patterns within a complex energy-water system. Highlights: An interval two-stage fuzzy credibility constrained programming model is developed. Dual uncertainties are reflected in terms of interval membership function. It is applied to planning energy-water nexus system in Tangshan, China. Results can provide in-depth insights into trade-offs among system economy and risk. The total water consumption control can accelerate energy structural adjustment.